Spatial Patterns of Housing Growth and Settlement in Saguling Lakeside Area (Study of Morphology and Physiography) - Ida Hamida; Wiwik Dwi Pratiwi; Esti Istiqomah (Universitas Kebangsaan Republik Indonesia [UKRI], 2019)
ABSTRACT :Water edges settlement development has always have strong relationship with its water bodies be it lake or river. For example, by the road–settlement would face the road as main transportation cum logistic facility. On the other hand, along water edges, settlements can either orientated facing water bodies or be positioned as on its back. These two types of orientations may influence mutual relations between water bodies and its settlements. These mutual relationship can be realized via its impact on both the water bodies and its settlements.Settlement development due to never ending increase of population has caused ever rising needs of housing provision.It has spread not only on urban areas but also on other cultivated areas such forest reserve edges, and major coastal areas. Waterfront areas have been increasly attractive settlement areas. There are many factors contributing to this phenomenon such as water as basic need of life, source of income, agriculture, water bodies as transportation facility, and last but not least its nature’s beauty.This research studies on settlement patterns at lakeside with case study of Lake/Dam Saguling which is located at West Bandung Regency of West Java. Apart from being Hydro Electrical Generator, Saguling Dam has been the surrounding areas water source and agriculture. Its water body patterns is widely spread and branched out to many surrounding districts. In some areas, it has become both informal and formal settlements. Settlement spatial pattern typology as been carried out through meticulous observation which relates natural condition and the menmade built environment as well as the lake-water bodies pattern.With this study on morphology and physiography on the water bodies, it is hoped that there shall be continuous study on its impact and mutual reaction between the lake and its settlement to conclude recommendation on policies, development plans, and sustainable management strategies that benefit both settlement and the lake as a sustainable water body.Keywords : Lakeside Settlement, Structure, Disperse/Spread Patterns, Lake Physio/Morphology